Sainte-Anne ou la Santé ? De l'enfermement des rebelles en France au XIXe siècle. Éléments de comparaison - Audrey Higelin; Marie Bergounioux (Criminocorpus)
A rebellious person is only considered as such against an establishment and a set of laws that define him or her as being opposed to a power. From the 1830s, in France, the debate regarding his/her place in society intensifies. The confinement appears as an obvious solution, but, in the light of recent progress of the young alienist science, prison, in its numerous forms, is no longer blatant. More and more, offenders and criminals will be considered as putative lunatics whose place should be in asylums.This article shall treat, on the one hand, of the lunatic as a social and medical rebel, focusing on epileptics, and on the other hand, of the offender through a diachronic evolution of  implemented legislative texts  and their practical architectural realization. Both confining device, prison and asylum, shall be compared. This study shall not extend the year 1905 and the parution of the Chaumié decree.